Identification of irisin immunoreactivity in porcupine (Hystrix cristata) adrenal glands and kidneys - Timurkaan, Sema; Gur, Fatih M.; Tarakci, Berrin Gencer; Yalcin, Mehmet H.; Girgin, Mustafa (Wiley, 2018)
Irisin, a novel peptide, was initially been shown to be expressed explicitly in the muscle tissues. We studied the presence of irisin immunoreactivity in porcupine adrenal glands and kidneys. Immunocytochemistry showed that irisin was localised both in the adrenal cortex and adrenal medulla. In organs, irisin immunoreactivity was found in the tubular and collecting system of the nephron. The functional role of irisin in the adrenal gland and kidney has not been precisely yet. However, irisin might have a paracrine and autocrine function as do other locally produced peptides.
Keywords: adrenal gland; immunoreactivity; irisin; kidney; porcupine